SOHLHs Might Be Gametogenesis-Specific bHLH Transcriptional Regulation Factors in Crassostrea gigas - Qian, Guang; Bao, Yongbo; Song, Danli; Chen, Na; Lin, Zhihua (Frontiers in Physiology, 2019)
The self-renewal and differentiation of germ cells are essential for gametogenesis and reproduction. In mammals, the transcription factors SOHLH1 and SOHLH2, two members of the bHLH family, are specifically expressed in the gonads, and play an important role in spermatocyte and oocyte differentiation. In our previous study, we performed a phylogenetic analysis of the Lophotrochozoa bHLH genes, and two Sohlh were identified in the Pacific oyster Crassostrea gigas. Based on the genomes of other species that have complete genomic information, we further analyzed the phylogenetics of the Sohlh in this study. The results indicate that the Sohlh are ancient genes that were lost in many species during evolution, including in some invertebrates, and lower vertebrates. The phylogenetic tree shows that Sohlh1 and Sohlh2 are located in different scaffolds and that they have low similarity, suggesting early separation in invertebrates. We used RNA-seq and RT-PCR to examine the mRNA expression of the Sohlh in C. gigas (termed Cg-Sohlh), we found that Cg-Sohlh1, and Cg-Sohlh2 are specifically expressed in the gonads. During gonadal development, the mRNA expression levels of both genes increased from the proliferative stage and reached the highest level at the growth stage (P < 0.05). Then, the expression level decreased until the resting stage. In addition, immunohistochemistry was used to determine that the Cg-SOHLH1 protein was specifically expressed in the spermatogonia and spermatocytes. Cg-Sohlh2 mRNA was expressed in both the male and female gonads, while Cg-Sohlh1 mRNA was highly expressed in the female gonads at all developmental stages except for the resting stage. These data indicate that Cg-SOHLH might be gonad-specific regulatory factors, similar to mammalian SOHLH, and that Cg-SOHLH1 might be involved in spermatogonial differentiation. This study lays the foundation to further determine the functional role of SOHLH in mollusk gametogenesis and provides a foundation to better understand the regulatory mechanism of gametogenesis in invertebrates.